MSX1-Induced Neural Crest-Like Reprogramming Promotes Melanoma Progression - Heppt, Markus V.; Wang, Joshua X.; Hristova, Denitsa M.; Wei, Zhi; Li, Ling; Evans, Brianna; Beqiri, Marilda; Zaman, Samir; Zhang, Jie; Irmler, Martin; Berking, Carola; Besch, Robert; et al. (Journal of Investigative Dermatology, 2018)
Melanoma cells share many biological properties with neural crest stem cells. Here we show that the homeodomain transcription factor MSX1, which is significantly correlated with melanoma disease progression, reprograms melanocytes and melanoma cells toward a neural crest precursor-like state. MSX1-reprogrammed normal human melanocytes express the neural crest marker p75 and become multipotent. MSX1 induces a phenotypic switch in melanoma, which is characterized by an oncogenic transition from an E-cadherin–high nonmigratory state toward a ZEB1-high invasive state. ZEB1 up-regulation is responsible for the MSX1-induced migratory phenotype in melanoma cells. Depletion of MSX1 significantly inhibits melanoma metastasis in vivo. These results show that neural crest-like reprogramming achieved by a single factor is a critical process for melanoma progression.
CRIS-Team Scopus Importer:2023-03-23